Venstrefløjens bibel – Kierkegaard og den slovenske skole - Larsen, Søren Bo Aggerbeck (Slagmark - Tidsskrift for idéhistorie, 2018)
This paper deals with the theological, philosophical and political issues that, in the train of thought from the Slovenien philosopher Slavoj Žižek, is to be sought in the ‘logic of incarnation’ at work in the Danish philosopher Søren Kierkegaard’s Philosophical Fragments. It also deals with the question of how to connect this framework with a new revival of the left. Following the argument of the two thinkers a joke of Monty Python will be put to the test and discussed as a coincidence of the ‘concrete universal’. What does the ‘concrete universal’ mean and how is it connected to Kierkegaard’s Christianity?